'GRAMMARLY' AS A TEACHERS' ALTERNATIVE IN EVALUATING NON -EFL STUDENTS WRITINGS - Tira Nur Fitria (UIN Raden Mas Said Surakarta, 2021)
In evaluating students’ EFL writing, lecturers nowadays can implement corrective evaluation by using an online automatic software. Grammarly is automated online software that is comonly used in EFL writing classes. It is an internet proofreading service that evaluates the correctness grammarl, spelling, punctuation, and vocabulary as well as detects plagiarism. This paper reports research aimed at exploring the use of Grammarly software for evaluating non-EFL students’ writings. This research employed descriptive-qualitative method with students of ITB AAS Indonesia as the data sources. The results of analysis show that in correcting students' language errors, lecturers can evaluate and analyze in details without a lot of correcting efforts or improvements. Grammarly can be considered as a useful tool for lecturers who need to correct non-EFL students’ writings. Grammarly will automatically check or detect the work being typed from various related aspects. Various writing errors made by the students were found in Grammarly’s reports, both in the aspect of correctness and clarity. Correctness is concerned with the mechanical norms in writing, whereas clarity deals with concise and direct language use. The spelling errors found in students’ writings are text inconsistencies, misspelled words, and improper formatting whereas for grammatical there are subject-verb disagreement, passive voice misuse, as well as unclear, wordy, and incomplete sentences. Meanwhile, the errors in punctuation are shown by inappropriate use of punctuation marks in compound/complex sentence, comma misuse within clauses, and improper formatting. It can be concluded that Grammarly can be an alternative for lecturers’ in evaluating non-EFL students' writings.